Morphological and Molecular Characterization of Kochinema farodai Baqri and Bohra, 2001 (Dorylaimida: Nordiidae) from California, with the First Molecular Study and an Updated Taxonomy of the Genus - Sergio Álvarez-Ortega (Animals, 2020)
This paper deals with the morphological and molecular characterization of Kochinema farodai Baqri and Bohra, 2001, with an integrative approach. The finding of K. faroidai in California is a remarkable biogeographical novelty, as it is the first American record of the species. Molecular data herein obtained represent the first molecular study of the genus Kochinema. Furthermore, scanning electron microscopy (SEM) observations of a member of Kochinema are provided for the first time. Additionally, this contribution provides new insights into the phylogeny and taxonomy of the nematode genus Kochinema. A brief historical outline of the matter is presented. Then, the morphological pattern of the genus is revised and illustrated, the anterior position of amphids, whose opening is located on lateral lip, being its most relevant diagnostic feature. The phylogenetic analysis inferred from D2–D3 expansion segments of 28S rRNA gene shows that Kochinema clustered together with other dorylaimid species characterized by the absence of pars refringens vaginae and that it does not share a recent common ancestor with other members of the family Nordiidae. A likely polyphyly of the family Nordiidae is confirmed. Finally, an updated taxonomy of the genus is proposed, including a revised diagnosis, a list of species, a key to species identification, and a compendium of their main morphometrics and distribution data.